Hemoglobin-to-red blood cell distribution width ratio as a protective factor against coronary artery disease: a cross-sectional analysis of NHANES (2011-2018) - Wang, Xin-Da; Li, Chaoya; Hu, Jia; Cao, Fen; Zhu, Li; Zhu, Yongzhi; Wen, Zhongzheng; Liu, Jun (Frontiers in Pharmacology, 2025)
BackgroundCoronary artery disease (CAD) is the leading cause of death worldwide, and inflammation is a significant factor in its development. While the hemoglobin-to-red blood cell distribution width ratio (HRR), an indicator of inflammation, has been linked to various diseases, its association with CAD is not well established.MethodsWe conducted an analysis using data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2011 to 2018. After excluding participants due to age, missing data, and potential confounding factors, 6,881 individuals were included in our study. CAD was identified through self-reported questionnaires, and HRR was determined from laboratory measurements. We controlled for factors such as hypertension, waist circumference, systolic blood pressure, fasting plasma glucose, and others in our logistic regression analysis to explore the relationship between HRR and CAD.ResultsWe found that higher HRR levels were associated with a lower risk of CAD. In our fully adjusted model, the odds ratios for CAD for the second, third, and fourth quartiles of HRR were 0.38, 0.42, and 0.51, respectively, compared to the first quartile (P < 0.001). An increase in HRR by one unit was associated with a 49% decrease in the likelihood of CAD. Furthermore, linear regression models indicated a 74% reduction in CAD risk for each one-unit increase in HRR (P = 0.0002). There was a notable threshold at HRR 1.02; beyond this point, each unit increase in HRR was associated with a 91% decrease in CAD odds. This suggests that for individuals with an HRR above 1.02, strategies to increase body water content and reduce blood viscosity could potentially lower their risk of developing CAD.ConclusionOur study revealed an inverse linear relationship between HRR and CAD risk, indicating that HRR may serve as a protective factor against CAD.